2018
DOI: 10.1080/0284186x.2018.1533647
|View full text |Cite
|
Sign up to set email alerts
|

Positive sentinel node in luminal A-like breast cancer patients - implications for adjuvant chemotherapy?

Abstract: Background: In luminal Alike breast cancer, the indication for adjuvant chemotherapy still is largely based on lymph nodestatus. Sentinel node (SN) positive patients who are no longer recommended an axillary lymph node dissection (ALND) risk undertreatment, especially if they have 4 lymph node metastases (LNMs). Aim: To quantify the group of SN positive luminal Alike patients with 4 LNMs and to investigate if the ratio between positive SNs and examined SNs (SN ratio) can provide information of the axillary tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Oncologists define luminal A as estrogen receptor (ER) > 1%, progesterone receptor (PR) ≥ 20%, breast cancer with negative human epidermal growth factor receptor-2 (HER2), and Ki-67 < 14% of clinical cases [4]. Luminal A has high hormone receptor expression, negative HER2 expression, and a low proliferation rate, properties that contribute to its better prognosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Oncologists define luminal A as estrogen receptor (ER) > 1%, progesterone receptor (PR) ≥ 20%, breast cancer with negative human epidermal growth factor receptor-2 (HER2), and Ki-67 < 14% of clinical cases [4]. Luminal A has high hormone receptor expression, negative HER2 expression, and a low proliferation rate, properties that contribute to its better prognosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…The associations between pN stage and both tumor size and T stage were shown in ER-positive/HER2-negative BC by Noda et al [ 33 ]. Several other authors have obtained similar results [ 45 ], but some did not show any relationships between tumor size and lymph node involvement in luminal A BC [ 46 ]. Our study showed that patient age does not correlate with lymph node involvement in this molecular subtype.…”
Section: Discussionmentioning
confidence: 66%
“…Previous breast cancer studies exploring the impact of nodal staging data on adjuvant treatment decision, have not specified the histological subtypes and are based on smaller cohorts than ours 42,43 36 . In the seminal trials, a majority of the included patients had micrometastasis only in their SLNs and isolated tumor cells were classified as micrometastasis 44 , and ≥ 90% of the patients received adjuvant systemic treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Previous breast cancer studies exploring the impact of nodal staging data on adjuvant treatment decision, have not specified the histological subtypes and are based on smaller cohorts than ours 42,43 Studies investigating ALN status in relation to histological subtype, have shown a higher axillary metastatic burden in ILC compared to NST, but the total number of patients with ILC, strictly eligible for omission of cALND according to the Z0011 criteria and with both SLN and non-SLN data available, is low (n = 2-24); and complete data from those meeting the St. Gallen 2019 guidelines are for the most part either missing or not reported 17,19,[45][46][47] .…”
Section: Discussionmentioning
confidence: 94%